Quality of Financial Reporting: Importance of Quality in Accounting Information System and Information Technology - Bramasto, Ari; Amelia, Alya (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
Quality of information system and information technology are two important factors in developing the quality of financial reporting. Functional accounting information system can produce accurate, relevant, and timely information. On the other hand, optimal information technology can support the accuracy of financial data arrangement along with information integrity and security. The purpose of this study is to determine the contribution and influence of the quality of information system and information technology on the quality of financial reporting implemented in the National Land Agency of Bandung Regency. The study uses a quantitative approach with collected primary data through questionnaires and data processing using SmartPLS 4.1.1.2. The results show that the quality of accounting information system contributes 46,9% to the quality of financial reporting while information technology contributes 51.2%.